Studi Evaluasi Kualitas Dan Status Trofik Air Waduk Selorejo Akibat Erupsi Gunung Kelud Untuk Budidaya Perikanan - Sayekti, Rini Wahyu; Yuliani, Emma; Bisri, Mohammad; Juwono, Pitojo Tri; Prasetyorini, Linda; Sonia, Fauzia; Putri, Ayu Pratama (Fakultas Teknik, Universitas Brawijaya, 2015)
Selorejo dam in Malang regency has been used as a water storage and for freshwater fishery. On February 13 th 2014, Mount Kelud was erupted and produced volcanic ash which fell into the reservoir and caused an imbalanced water quality.The research was conducted in order to (a) observe a comparison between field measurement (temperature, turbidity, DO, pH, ammonia, nitrite, nitrate, total-P, Cu, Zn, Pb, Cr, and silica) and water quality standard in both upstream and middle station,(b) to determine time interval needed by each parameter to meet permitted value for freshwater fishery, (c) to determine water quality status using Pollution Index method, (d) to determine main contributors to the water pollution, (e) to determine trophic status index of Selorejo dam prior to and after the eruption, and (f) to analyze trophic status index fluctuation and pollution load capacity after the eruption.Method that was used to determine water quality status was Pollution Index. Trophic status index determined by comparing trophic status index standard on PerMenLH tahun 2009 with total-P, NO3N, chlorophyll a, and water clarity.The result from this research shows (a) before eruption, 40% of field measurement in upstream station and 28% of field measurement in middle station do not meet the standard values required. After eruption, 31% of field measurement in upstream station and 36% of field measurement in middle station do not meet the standard values required, (b) time interval needed for each parameters to meet permitted values are 111 days (pH and nitrate), 71 days (DO), 54 days (turbidity), while total-P and silica have not meet the required values up to the end of observation period, (c) water quality status in Selorejo dam on both stations are â€œLightly pollutedâ€, before and after the eruption of Mount Kelud, (d) main contributors to the water pollution on upstream station are total-P and nitrate. On middle station, the main contributors are total-P, silica, and nitrate, (e) Trophic status index of Selorejo dam is â€œhypereutrophicâ€ for chlorophyll a, (f) pollution load capacity of Selorejo dam for total-P is 12.072, 58 kg P/year and has to be increased 69, 61% to 39.722, 33 kg P/year to lower trophic status index to â€œOligotrophicâ€.Keywords: Water quality, water quality status, trophic status index, load capacity index, pollution index